2020
DOI: 10.1016/j.foodchem.2019.126024
|View full text |Cite
|
Sign up to set email alerts
|

The lipid type affects the in vitro digestibility and β-carotene bioaccessibility of liquid or solid lipid nanoparticles

Abstract: Solid lipid nanoparticles (SLNs) are emulsion-based carriers of lipophilic bioactive compounds. However, their digestibility may be affected by the solid lipid phase composition. Hence, the aim of this work was to study the in vitro lipolysis kinetics as well as the relationship between the lipid digestion, micelle fraction composition and βcarotene bioaccessibility of SLNs with different solid lipids, being blends of medium chain triglyceride (MCT) oil, glyceryl stearate (GS) or hydrogenated palm oil (HPO) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…Lipid composition also affects the in vitro digestibility of SLNs. SLNs formulated with medium-chain triglyceride oil and glyceryl stearate can be fully digested, whereas those formulated with medium-chain triglyceride oil and hydrogenated palm oil exhibit slower lipolysis kinetics and higher β-carotene bioaccessibility [165]. The reason is that the presence of monounsaturated long-chain fatty acids after digestion of hydrogenated palm oil-containing SLNs enhances the solubilization capacity of the mixed micelles for β-carotene.…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%
“…Lipid composition also affects the in vitro digestibility of SLNs. SLNs formulated with medium-chain triglyceride oil and glyceryl stearate can be fully digested, whereas those formulated with medium-chain triglyceride oil and hydrogenated palm oil exhibit slower lipolysis kinetics and higher β-carotene bioaccessibility [165]. The reason is that the presence of monounsaturated long-chain fatty acids after digestion of hydrogenated palm oil-containing SLNs enhances the solubilization capacity of the mixed micelles for β-carotene.…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%
“…2c ). One possible explanation was that FFAs released from PGFEs hydrolysis may participate in the formation of micelles, resulting in higher levels of micelles [ 23 ]. On the other hand, an opposite change in the particle size distributions occurred with an increase in the aliphatic chain lengths of PGEFs, which may be ascribed to the fact that FFAs generated from longer aliphatic chain of PGFEs were prone to form insoluble calcium soaps induced by calcium ions [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…A three-parameter logistic model has been developed to elucidate the amount of FFAs released as a function of digestion time [ 23 ]. In the present study, released FFAs (%) during lipolysis was fitted to the following formula using a nonlinear analysis in Origin 9.0 software (Origin Lab, Northampton, Massachusetts, USA): where C(t) is released FFAs (%) when digestion time is t, C f is the asymptotic value when digestion time is ∞, k is the rate constant (min −1 ), Tc is the time to achieve effective lipolysis where half the FFAs are released (min).…”
Section: Methodsmentioning
confidence: 99%
“…Bonnaire et al (2008) reported that, besides the influence of lipid physical state on lipase adsorption to the droplet surface, where typically liquid lipids promote a better lipase's adsorption than the solid lipids, the spatial organization of lipid molecules can influence lipase ability to hydrolyze the triacylglycerols, once the triglycerides crystals can present different polymorphs, namely the β-form which is the densest polymorphic form (Himawan, Starov, & Stapley, 2006). Other authors observed that, besides the lipid's physical state, the chain length of the fatty acids in the lipid composition has a high impact in the FFA release and therefore in the lipid digestion degree (Helena de Abreu-Martins, Artiga-Artigas, Hilsdorf Piccoli, Martín-Belloso, & Salvia-Trujillo, 2020).…”
Section: Ffa Releasementioning
confidence: 99%
“…SLN presented the lowest bioaccessibility probably due to the composition of the mixed micelles produced and their solubilization capacity. Helena de Abreu-Martins et al (2020) studied the lipolysis kinetics, micelle fraction composition and the β-carotene bioaccessibility of SLN with different solid lipids and observed that besides the lipid digestion extent, the mixed micelles composition has a high impact on the β-carotene bioaccessibility. Also, the results from the present work are in accordance with other studies that reported that bioactive compounds loaded on particles produced with liquid lipids showed higher bioaccessibility than particles produced with solid lipids (Aditya et al, 2014).…”
Section: Bioaccessibility Stability and Effective Bioavailabilitymentioning
confidence: 99%